Effects of coagulants, processing variables and milky extract of kenaf seed-to-soybean ratios on the physicochemical property and texture profile of kenaf (Hibiscus cannabinus L.) seed-based tofu - Giwa, Ibrahim Shafa'atu (2021)
Kenaf (Hibiscus cannabinus) is a multipurpose herbaceous plant of economic significance. Attention on the kenaf plant has focused mainly on the stem for fiberbased industries. Also, the leaves have received little applications in herbal medicine, while the seed has been underutilised despite its high nutritional value especially as raw material and/or ingredient for the food sector. This study attempted to value-add kenaf seed as raw material for tofu production. In view of this, the objectives of this study were (i) to determine the effects of soaking temperatures on hydration time, microstructure, chemical composition of the kenaf seed and the physicochemical quality of its milky extracts; (ii) to evaluate the effects of coagulants and processing variables on the quality of kenaf seed tofu; (iii) to improve the quality of kenaf seed tofu by partly substituting kenaf seed with soybean; and (iv) to investigate the mechanism of coagulation of kenaf seed tofu and kenaf seed-soybean tofu blend in comparison to soybean tofu. Results on the effects of soaking temperatures study revealed that raising the soaking temperature of water from 25 to 65 oC significantly increased the rate of water absorption from 0.009 to 0.068 min-1, and subsequently decreased the soaking time from 616 to 160 min. However, increased in the soaking temperature had no significant effect on the proximate composition of the kenaf seeds and the milky extracts; but, soaking treatment in combination with extraction process significantly reduced the phytic acid, tannic acid and trypsin inhibitors concentrations from 2.74 %, 0.082 mg/mL and 11.18 mg/g of the un-soaked seed to 1.94-2.11 %, 0.031-0.052 mg/mL and 9.24-10.34 mg/g in milky extracts, respectively. The result of screening stage during the characterisation phase of kenaf seed tofu development indicated that the main and interactions effects of seed-towater ratio for extraction of kenaf seed milky extract, coagulant types and concentrations, and temperature of milky extract at the point of addition of coagulant significantly affected the physicochemical property and texture profile analysis of the kenaf seed tofu. The results of the optimisation phase of the kenaf seed tofu production indicated that the optimum setting condition of coagulants and soaking temperature of kenaf seed for production of optimum tofu are by soaking the kenaf seed at 25 oC (ambient temperature) and addition of 1.00 g/% potash as the coagulating agent. At this optimised condition, the yield of tofu was 64.69 g/100g, whereas the hardness, chewiness, springiness and cohesiveness tofu properties were 10130 g, 944.90, 0.64 mm and 0.19, respectively. Substitution of kenaf seed with soybean at five different ratios of kenaf seed-to-soybean (K-S) of 50:50, 60:40, 70:30, 80:20 and 90:10 were found to increase the tofu yield significantly as the amount of soybean in the tofu blend was increased. The order of increment in the yield was 90K:10S (66.24-89.84 g/100g) < 80K:20S (88.89-129.67 g/100g) < 70K:30S (101.53-134.19 g/100g) < 60K:40S (152.19-197.32 g/100g) < 50K:50S (158.76-204.61 g/100g). The result of the finding showed that the protein content of the K-S tofu was significantly increased from 36.17 g/100g in 100 % kenaf seed (100%K) tofu to a range of 40.84-45.36 g/100g in the tofu blend. Beside that, the KS tofu made from blend of kenaf seed to soybean in the ratios of 50:50, 60:40 and 70:30 had similar protein content with 100 % soybean (100%S) tofu, but a significantly higher in fat content of 16-30 % increment. The ratio of total essential amino acid to total amino acid in the K-S tofu was significantly improved from 35 % in 100%K tofu to 46 % in the K-S tofu. The scanning electron microscopic images of the K-S tofu revealed that increasing the proportion of soybean in the tofu blend produced a tofu with homogeneous, denser, continuous and consistent network of smaller pore sizes that favours water entrapment within the gel matrix. The best KS tofu can be produced from 70K:30S blend without compromising the textural profile and physicochemical properties. The mechanism of coagulation of the tofu showed that 100%K tofu had no disulphide (-S-S-) bond and this accounted for the loose nature of the curd. Furthermore, the 100%K tofu had a slower coagulation rate with a significantly lower final storage modulus (G'f) of 0.41 Pa. However, substitution of 30 % of the kenaf seed with soybean brought about formation of -SS- bonds, including an improvement in the coagulation rate with a G'f of 1.13 Pa. Likewise, 30 % substitution of kenaf seed with soybean decreased the coagulation temperature from 75 oC in 100%K tofu to 71 oC in the K-S tofu. The present of β‐ sheet structure in all the tofu studied accounted for the hardness characteristic of the tofu.